LEXIC-SEMANTIC FEATURES OF APHORISMS SYSTEMS - Ruziev Khusniddin Bakhritdinovich (American Journals Publishing, 2024)
This article deal with lexic-semantic features of aphorisms. Linguistic sciences’ opinion are given and semantic categories of aphorisms are discussed.
Keywords: aphorisms, linguistic term, semantic content, metaphor, metonymy, hyperbole.